A new single‐urea‐bound 3, 5‐dimethylphenylcarbamoylated β‐cyclodextrin chiral stationary phase and its enhanced separation performance in normal‐phase liquid chromatography. Issue 2 (10th November 2017) - Lin, Chun; Fan, Jun; Liu, Wenna; Chen, Xiaodong; Ruan, Lijun; Zhang, Weiguang
Abstract: A new single‐urea‐bound chiral stationary phase based on 3, 5‐dimethylphenylcarbamoylated β‐cyclodextrin was prepared through the Staudinger reaction of mono (6 A ‐azido‐6 A ‐deoxy)‐per(3, 5‐dimethylphenylcarbamoylated) β‐cyclodextrin and 3‐aminopropyl silica gel under CO2 atmosphere. The new phase exhibited good enantioseparation performance for 33 analytes using normal‐phase HPLC conditions; 19 of them were baseline separated. Effects of structure of analytes, alcoholic modifiers, and acidic/basic additives on separation performances of this new cyclodextrin chiral stationary phase have been studied in detail. The results showed that the retention and resolution of acidic and basic analytes on the CSP were greatly affected by the additives. Peak symmetry for some analytes could be improved by simultaneously adding acidic and basic additives to the mobile phase. This work expands the potential applications of the cyclodextrin‐based chiral stationary phases in the normal‐phase HPLC.